Framing sustainable lifestyles : organic consumption in a women's magazine - Sarja, Sessa Milla (2017)
Forms of sustainable lifestyles and more responsible ways to consume have become more popular in recent years. This is reflected also in that mainstream media discusses about sustainability. Similarly, there is a growing interest on organic produce, the organic market has grown steadily from the turn of the century. Due to the growing popularity of sustainability, the way media communicates about the issue, is of interest. This thesis studied how women’s magazines communicate about sustainable lifestyles, and sustainability in general. Especially, how the use of organic goods is reasoned and presented in a magazine is studied. The aim of the thesis was to uncover the frames, which the magazine used to communicate their view on organics. The study was conducted as a qualitative document analysis with a longitudinal approach. The theoretical framework was built on the concepts of sustainable lifestyle and analysed by the frame analysis method. Particularly, the frame devices presented by Robert Entman were utilised in analysing the data. Research data was derived from a Finnish women’s magazine MeNaiset. The data presented a mainstream media outlet, reflecting the views of the Finnish society. The results suggest that organics are associated with health, ethics, trends and presented also as options. The findings support a common view that women’s magazines mostly focus on promoting sustainable lifestyles by means of green consumerism. Their motives rise from the need to support the current status quo i.e. society’s support of consumer culture. This study contributes to the knowledge that currently women’s magazines tend to maintain the status quo and fail to communicate sustainability in a way, which would be more sustainable in long term.